2007
DOI: 10.1111/j.1423-0410.2007.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of buffy‐coat‐derived platelets in additive solutions at 4 °C and 22 °C: flow cytometry analysis of platelet glycoprotein expression

Abstract: Platelets stored at 4 degrees C retain their in vitro characteristics better than those stored at 22 degrees C, except for parameters that reflect changes in shape. Storage at 4 degrees C is not associated with an increased expression of glycoprotein (GpIb, GpIIb/IIIa) and platelet activation markers (CD62p and CD63) as compared with storage at 22 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 36 publications
7
83
0
1
Order By: Relevance
“…The single platelets showed no changes in GPIb expression as shown previously [13,28] but there are also studies reporting a decrease in the expression of GPIb during storage [29,30].…”
Section: Discussionmentioning
confidence: 52%
“…The single platelets showed no changes in GPIb expression as shown previously [13,28] but there are also studies reporting a decrease in the expression of GPIb during storage [29,30].…”
Section: Discussionmentioning
confidence: 52%
“…Horstman and Ahn [13] showed that many of the platelet-specific glycoproteins are routinely identified on PMP, chiefly gpIIbIIIa and gpIb. Sandgren et al [19] reported that no significant difference in gpIIb/IIIa expression was detected over time whereas the percentage of platelets expressing gpIba gradually decreased at 22°C. In our study, the significantly decrease in the levels of both gpIba and gpIIb/IIIa was demonstrated on the nPMP during 7 days storage of PCs (P value = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Les conditions de conservation et en particulier la température de stockage semble être aussi un facteur non négligeable de variation pour l'expression de facteurs inflammatoires, mais ce point est peu étudié dans les pays soumis à fortes contraintes réglementaires. Certains systèmes transfusionnels étrangers autorisent néanmoins la déli-vrance de plaquettes conservées à 4 • C et ce point pourrait être pris en considération [40][41][42]. Enfin, les plaquettes activées libèrent des microparticules (MP) [43] qui contiennent de très grandes quantités de facteurs membranaires et plasmatiques d'activation ainsi que des facteurs d'hémostase [44,45].…”
Section: Lésions De Préparation Et De Stockage Et Celles Liées Au VIunclassified